Obligation in exile the Jewish diaspora, Israel and critique - Baron, Ilan Zvi 1978- (Edinburgh University Press, 2015)
Explores the complex relationship between Israel and the Diaspora Jewish identityCombining political theory and sociological interviews spanning four countries, Israel, the USA, Canada and the UK, Ilan Zvi Baron explores the Jewish Diaspora/Israel relationship and suggests that instead of looking at Diaspora Jews' relationship with Israel as a matter of loyalty, it is one of obligation. Baron develops an outline for a theory of transnational political obligation and, in the process, provides an alternative way to understand and explore the Diaspora/Israel relationship than one mired in partisan debates about whether or not being a good Jew means supporting Israel. He concludes by arguing that critique of Israel is not just about Israeli policy, but about what it means to be a Diaspora Jew
Title from publisher's bibliographic system (viewed on 09 Sep 2016)
Keywords: Juden; Israel and the diaspora; Jews / Attitudes toward Israel; Political obligation; Jews / Identity; Jewish diaspora; Ethnische Identität; Nationale Minderheit; Politisches Handeln; Israel / Foreign public opinion